2023
DOI: 10.3390/ijms24054473
|View full text |Cite
|
Sign up to set email alerts
|

DNA Nanomachine (DNM) Biplex Assay for Differentiating Bacillus cereus Species

Abstract: Conventional methods for the detection and differentiation of Bacillus cereus group species have drawbacks mostly due to the complexity of genetic discrimination between the Bacillus cereus species. Here, we describe a simple and straightforward assay based on the detected unamplified bacterial 16S rRNA by DNA nanomachine (DNM). The assay uses a universal fluorescent reporter and four all-DNA binding fragments, three of which are responsible for “opening up” the folded rRNA while the fourth stand is responsibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 70 publications
1
0
0
Order By: Relevance
“…The results showed that HDNM is highly selective as it did not produce significant fluorescence even when incubated with high concentrations of the nonspecific Influenza A virus for 3 h at 55 °C (Figure ). This high selectivity is consistent with prior studies on binary probes based on deoxyribozyme 10–23, among other binary probes, , proving their excellent selectivity, which is relevant to their applications in single-nucleotide polymorphisms (SNP) genotyping, and it makes it a promising candidate for virus detection and diagnosis, contributing significantly to public health efforts.…”
supporting
confidence: 83%
“…The results showed that HDNM is highly selective as it did not produce significant fluorescence even when incubated with high concentrations of the nonspecific Influenza A virus for 3 h at 55 °C (Figure ). This high selectivity is consistent with prior studies on binary probes based on deoxyribozyme 10–23, among other binary probes, , proving their excellent selectivity, which is relevant to their applications in single-nucleotide polymorphisms (SNP) genotyping, and it makes it a promising candidate for virus detection and diagnosis, contributing significantly to public health efforts.…”
supporting
confidence: 83%